EFFECTIVENESS OF BREATHING EXERCISES IN ELDERLY TUBERCULOSIS PATIENTS IN MEDAN - sulaiman; Nurmaini Achamd; Evi Naria; Kintoko R. Rochadi (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Introduction. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. It is a significant global public health problem. The purpose of this study was to assess the effectiveness of the collaboration of diaphragmatic breathing exercises and pursed lip breathing and medical drugs with medical therapy without breathing exercises on reducing shortness of breath at the Helvetia Lung Specialized Hospital, Medan. Methods. Research design with Quasi Experiment with pretest-posttest approach with two group control, 30 respondents with nonprobability sampling technique with purposive sampling method. Results: after getting medicamentous drugs, the value of tightness decreased with a significance value of p = 0.001 (p = 0.05). After getting drug administration collaborating diaphragm breathing and pursed lip breathing exercise, the value of tightness decreased with a significance value of p = 0.001 (p = 0.05). Respondents who received drug corabolation and diaphragm breathing and pursed lip breathing exercise proved the difference in the value of reducing tightness was higher than patients who were only given medicamentous drug therapy with a significance value of p = 0.011 (p = 0.05). Conclusion: the administration of drugs in collaboration with diaphragm breathing and pursed lip breathing exercise is more effective in reducing shortness of breath compared to the administration of medical drugs without breathing exercises.